Partisipasi Masyarakat Kelompok Sadar Wisata Terhadap Peningkatan Kesejahteraan Pada Objek Wisata Buatan di Kota Balikpapan - Rissa Raehana Purwanto; Yesi Aprianti (STIE Pariwisata API Yogyakarta, 2025)
The purpose of this study is: To find out how the role of Pokdarwis in improving the welfare of the community around artificial tourist attractions in Balikpapan City, in addition to that this study is also aimed at seeing how the positive impact given by the participation of the Pokdarwis community to improve community welfare, both of these things are complemented by the Pokdarwis who work to have a fixed income or additional income. The problems that are often faced by a community institution are usually caused by a lack of participation. The form of community participation is contained in the form of institutions, namely Pokdarwis which plays a role as a driver and facilitator in the development of tourist destinations. Therefore, this study is needed to examine the role of Pokdarwis as a community institution that can be a forum for the development of an artificial tourist attraction in the city of Balikpapan. This research method uses a type of qualitative research with a descriptive approach with data collection through observation, interviews and documentation as well as, the target of this study is the management of Pokdarwis, the Regional Government, and the Surrounding Community. The results of the study found that institutions are a forum for the development of tourism and the welfare of the surrounding community. Pokdarwis plays a role as an official institution that bridges the channels of assistance from the government and the realization of community needs for the development of tourist destinations which ultimately have an impact on the community's economy in a sustainable manner.